Terrigenous inputs link nutrient dynamics to microbial communities in a tropical lagoon - Christian John; Nyssa J. Silbiger; Thomas C. Adam; Danielle M. Barnas; Kalia S. Bistolas; Robert C. Carpenter; Noe Castañeda; Megan J. Donahue; Mary K. Donovan; Lauren N. Enright; Hannah E. Epstein; Jordan P. Gallagher; et al. (Limnology and Oceanography, 2025)
Nutrient availability drives community structure and ecosystem processes, especially in tropical lagoons that are typically oligotrophic but often receive allochthonous inputs from land. Terrestrially derived nutrients are introduced to tropical lagoons by surface runoff and submarine groundwater discharge, which are influenced by seasonal precipitation. However, terrigenous inputs presumably diminish along the onshore–offshore gradients within lagoons. We characterized nutrient availability in the lagoons of a tropical high island, Moorea, French Polynesia, using spatially distributed measurements of nitrogen content in the tissues of a widespread macroalga during the rainy season over 4 yr. We used synoptic water column sampling to identify associations among macroalgal nutrient content and the composition of inorganic macronutrients, dissolved organic matter, and microbial communities. We paired these data with quantifications of land use in nearby watersheds to uncover links between terrestrial factors, aquatic chemistry, and microbial communities. Algal N content was highest near shore and near large, human‐impacted watersheds, and lower at offshore sites. Sites with high algal N had water columns with high nitrite + nitrate, silicate, and increased humic organic matter (based on a fluorescence Humification Index), especially following rain. Microbial communities were differentiated among nearshore habitats and covaried with algal N and water chemistry, supporting the hypothesis that terrigenous nutrient enrichment shapes microbial dynamics in otherwise oligotrophic tropical lagoons. This study reveals that land–sea connections create nutrient subsidies that are important for lagoon biogeochemistry and microbiology, indicating that future changes in land use or precipitation will modify ecosystem processes in tropical lagoons.

Habitats and fish communities at mesophotic depths in the Mexican Pacific - Jordan A. Hollarsmith; Georgina Ramírez‐Ortiz; Tallulah Winquist; Manuel Velasco‐Lozano; Katherine DuBois; Héctor Reyes‐Bonilla; Kyle C. Neumann; Edwin D. Grosholz (Journal of Biogeography, 2020)
Aim Mesophotic ecosystems, found at the limit of light penetration in the ocean, are rich in biodiversity and harbour unique ecological communities. However, they remain among the least studied habitat zones on earth due to the high costs and technological limitations. Here, we characterize mesophotic communities in two marine reserves across a range of habitat types, depths and temperatures using submersible technologies, with the goal of understanding the processes that structure these communities across biogeographical regions. Location The Bay of La Paz and the Revillagigedo Archipelago, Mexico. Taxa Fish and algal species. Methods We used a small and inexpensive remotely operated vehicle (ROV) to conduct roving‐swim surveys of major habitat types in depths from 12 to 94 m. With the resulting binary data on the presence of fish species, we used generalized linear mixed models and canonical correspondence analysis to determine whether biogenic habitat, depth and/or temperature best explained species richness and community structure across reef and non‐reef substrate. Results We identified 72 species or genera, including new depth records for nine fish species and a new geographical record for one fish species. Our surveys included large undocumented rhodolith beds (free‐living coralline algae) and mesophotic algal communities, in addition to diverse communities of soft corals and sponges. Fish species richness was positively associated with rocky substrate and warmer water, and reef fish communities differed significantly by depth, temperature and biogenic habitat. Main conclusion Our results highlight the importance of biogenic habitat in structuring communities across gradients of depth and temperature. We also demonstrate the effectiveness of a small and economical ROV for conducting mesophotic surveys in remote regions. Our methods and results provide a framework that can be used to greatly increase the biogeographical and taxonomic scope of mesophotic research, especially for readily identifiable taxa such as fish.